Europe : privilege and protest, 1730-1789 - Hufton, Olwen H. (Blackwell classic histories of Europe, 1980)
"In the eighteenth century the claims of monarchs and even privileged aristocracies to unquestioned obedience and of the Church to a monopoly of truth were challenged by an increasingly secular and literate society. Reason, the rights of the individual to freedom from arbitrary government and increased tolerance shaped discourses of opposition. A growing population pressing on food supplies and the fiscal demands of governments with expansionist ambitions in America, Asia or central and eastern Europe contributed to confrontation and dissent." "Professor Hufton provides a fascinating account of the undermining of an archaic social order, top heavy with courts, bureaucracies and standing armies in different European contexts. She demonstrates how privilege was countered with protests which provoked constitutional crises and generated popular violence precipitating Europe into an age of revolution."--BOOK JACKET.